Clarifying Recent Adaptive Diversification of the Chrysanthemum-Group on the Basis of an Updated Multilocus Phylogeny of Subtribe Artemisiinae (Asteraceae: Anthemideae) - Shen, Chu-Ze; Zhang, Chu-Jie; Chen, Jie; Guo, Yan-Ping (Frontiers in Plant Science, 2021)
Understanding the roles played by geography and ecology in driving species diversification and in the maintenance of species cohesion is the central objective of evolutionary and ecological studies. The multi-phased orogenesis of the Qinghai-Tibetan Plateau (QTP) and global climate changes over late-Miocene has profoundly influenced the environments and evolution of organisms in this region and the vast areas of Asia. In this study, we investigate the lineage diversification of the Chrysanthemum group in Subtribe Artemisiinae (Asteraceae) likely under the effects of climate changes during this period. Using DNA sequences of seven low-copy nuclear loci and nrITS, and the coalescent analytical methods, a time-calibrated phylogeny of Subtribe Artemisiinae was reconstructed with emphasis on the Chrysanthemum group. The monophyletic Chrysanthemum group was well resolved into two major clades corresponding to Chrysanthemum and Ajania, two genera which can be well identified by capitulum morphology but have been intermingled in previous plastid and ITS trees. Within Chrysanthemum, a later divergence between the Ch. indicum complex and the Ch. zawadskii complex can be recognized. The time frames of these sequential divergences coincide with the late Cenozoic uplift of the Northern QTP and the concomitant climatic heterogeneity between eastern and inland Asia. Reconstruction of historical biogeography suggested the origin of the Chrysanthemum group in Central Asia, followed by eastward migration of Chrysanthemum and in situ diversification of Ajania. Within Chrysanthemum, the Ch. indicum complex and the Ch. zawadskii complex exhibited contemporary distributional division, the former in more southern and the latter in more northern regions. The geographic structure of the three lineages the Chrysanthemum group might have been associated with the climatic differentiation, and the polymorphisms in capitulum architectures should have facilitated adaptive diversification of the Chrysanthemum group under environmental heterogenization in Asia interior.